Combined quantum state preparation and laser cooling of a continuous beam of cold atoms - Di Domenico, Gianni; Devenoges, Laurent; Dumas, Claire; Thomann, Pierre (My University, 2010)
We use two-laser optical pumping on a continuous atomic fountain in order to prepare cold cesium atoms in the same quantum ground state. A first laser excites the F=4 ground state to pump the atoms toward F=3 while a second π -polarized laser excites the F=3 -> F'=3 transition of the D2 line to produce Zeeman pumping toward m=0. To avoid trap states, we implement the first laser in a 2D optical lattice geometry, thereby creating polarization gradients. This configuration has the advantage of simultaneously producing Sisyphus cooling when the optical lattice laser is tuned between the F=4 -> F'=4 and F=4 -> F'=5 transitions of the D2 line, which is important to remove the heat produced by optical pumping. Detuning the frequency of the second π-polarized laser reveals the action of a new mechanism improving both laser cooling and state preparation efficiency. A physical interpretation of this mechanism is discussed.